DAMPAK INTERNAL PERUSAHAAN DAN KONEKSI POLITIK TERHADAP BIAYA AUDIT - Martinus Martinus; Kurniawati Kurniawati (Jurnal Aplikasi Akuntansi, 2023)
This research aims to analyze the influence of audit committee, company complexity, political connection, and company risk on audit fee. The population of this research are financial sompanies listed on the Indonesia Stock Exchange in 2018-2021. The sample selection used a purposive sampling technique in accordance with predetermined criteria. Samples that met the criteria were 54 companies which produced 208 sample data. Hypothesis testing was carried out using multiple linear regression analysis with a significance level of 5%. The results of this research show that company complexity, political connection, and company risk have a positive and significant effect on audit fee.  Meanwhile audit committee has negative significant  effect on audit fee.